2000
DOI: 10.2188/jea.10.163
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E, Methylenetetrahydrofolate Reductase(MTHFR) Mutation and the Risk of Senile Dementia. An Epidemiological Study Using the Polymerase Chain Reaction(PCR) Method.

Abstract: We examined apolipoprotein E (Apo E) polymorphism and methylenetetrahydrofolate reductase (MTHFR) 677 C to T mutation by using the polymerase chain reaction (PCR) method in 100 elderly Japanese aged 60 or more, and assessed whether these genetic factors are associated with an increased risk for the clinical phenotypes of senile dementia, Alzheimer's disease (AD) and vascular dementia (VD) by cross-sectional survey. It was found that the Apo E * 4 allele were associated with an increased prevalence of AD as pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 20 publications
6
28
0
1
Order By: Relevance
“…17,25 Although we did not analyze cognitive function in the present study, an association between impaired cognitive function and SBI and white matter lesions has also been reported. 14,22 In several studies, the MTHFR TT genotype has also been demonstrated to be a risk factor for dementia, 26,27 although conflicting results have also been reported. 28,29 These findings suggest a possible association between the MTHFR TT genotype and cognitive impairment in the general population.…”
Section: Kohara Et Al Mthfr Gene and Silent Brain Infarctsmentioning
confidence: 99%
“…17,25 Although we did not analyze cognitive function in the present study, an association between impaired cognitive function and SBI and white matter lesions has also been reported. 14,22 In several studies, the MTHFR TT genotype has also been demonstrated to be a risk factor for dementia, 26,27 although conflicting results have also been reported. 28,29 These findings suggest a possible association between the MTHFR TT genotype and cognitive impairment in the general population.…”
Section: Kohara Et Al Mthfr Gene and Silent Brain Infarctsmentioning
confidence: 99%
“…Blood samples were stored at 20 o C for analysis. APOE genotyping was performed by amplification of the third exon of the APOE gene by polymerase chain reaction (PCR) with primers described by Wenham et al 23 , followed by an enzymatic clivage with the restriction enzyme HhaI (RFLP) 20 . Fragments of 72bp and 48bp are produced in APOE4, fragments of 91bp and 83bp are produced in APOE2 an 91bp and 48bp are generated in APOE3.…”
Section: Methodsmentioning
confidence: 99%
“…It has been recently reported a C677T mutation on the MTHFR gene which produces a thermolabile variant. In its homozygous form, this variant possesses a reduced overall enzyme activity to less than 30% of normal, resulting on increased serum homocysteine levels 9,20 . We examined both the APOE polymorphism and MTHFR mutation in a group of AD individuals and in controls, to assess whether these genetic factors increase the risk for this illness.…”
mentioning
confidence: 99%
“…MTHFR polymorphism causes decreased enzymatic activity of MTHFR and increased of the plasma total homocysteine level. Mutation in MTHFR is slightly associated with the onset of senile dementia (Nishiyama et al, 2000). Genotypes and haplotypes of the MTHFR have important implication for the pathogenesis of AD (Bi et al, 2009;Dorszewska et al, 2007;Gorgone et al, 2009;Kim et al, 2008;Wakutani et al, 2004).…”
Section: Methylenetetrahydrofolate Reductasementioning
confidence: 99%